SOME SOCIO-PSYCHOLOGICAL ASPECTS OF MEDIATION IN CIVIL LEGAL ISSUES - Manukyan , H.V. (Modern Psychology, 2020)
The establishment of the institution of mediation is associated with a complex of legal, social, economic and psychological factors. The study aims to determine the level of awareness of the phenomenon of mediation among students and teachers of Armenian universities, as well as their attitude to the professional competencies of mediators. The survey showed that most of the subjects are not aware of the role and main functions of the mediation system. A high degree of distrust in the institution of mediation was also revealed. According to the results of the survey, important professional skills are identified that are necessary for effective mediation in civil disputes.